Supercharged supply chains : discover unparalleled business planning and execution practices - Correll, James G.; Snowden, Lloyd; Bentzley, Jim (John Wiley & Sons, Inc., 2021)
"Supercharged Supply Chains is based on one of Oliver Wight's most popular classes that focused on Class A processes and the people/behaviors that are required to operate MRP effectively. The operating principles in the book are supported by war stories that point out why typical approaches don't work and why Oliver Wight processes succeed. After 25 years of teaching their most popular class, it is the war stories that help clients remember the principles. This book will help companies keep on track to successfully operate Business Excellence Planning. Business Excellence Planning is featured in every chapter, and it replaces MRPII as the new model supporting the 7th Edition Standard and the Milestone Workbooks. The book will also serve as a marketing tool for Oliver Wight and provide a much-needed resource for public and private classes."--